Handbook of research on retailing techniques for optimal consumer engagement and experiences - Musso, Fabio, 1960-; Druica, Elena, 1971- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2020)
"This book examines the application of present-day customer relationship management within the retail industry. It also explores in-depth merchandiser knowledge as well as the methods behind positive retailer-consumer relationships"--Provided by publisher.